Shear strength of orthodontic bracket bonding with GIC bonding agent after the application of CPP-ACPF paste - Melisa Budipramana; Thalca Hamid; Sianiwati Goenharto (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: White spot lesion is a major problem during fixed orthodontic treatment. This problem can be solved by minimizing white spot lesion before the treatment and using a fluoride-releasing bonding agent. The application of casein phosphopeptidesamorphous calcium phospate fluoride (CPP-ACPF) paste as remineralization agent before treatment and GIC as orthodontic bonding agent is expected to overcome this problem as well as to strengthen GIC bonding. Purpose: To measure the shear strength of fix orthodontic appliance using GIC bonding with CPP-ACPF application prior treatment. Methods: In this study, 50 extracted premolars were randomly divided into 2 groups: group 1 as treatment group and group II as control group that was not given CPPACPF pretreatment. After having been cut and put into acrylic device, the samples in group I were given pretreatment with CPP-ACPF paste on enamel surface for 2 minutes twice a day as instructed in product label for 14 days. Orthodontic brackets were bonded with GIC bonding agent on all samples in both groups as instructed in product label. Then, the shear strength was measured by Autograph Shimatzu with crosshead speed 0.5 mm/minute. The data was analyzed with Independent t-test. Results: The mean shear bond strength in treatment group was 19.22 ± 4.04 MPa and in control group was 12.97 ± 3.97 MPa. Independent t-test analysis showed that there was a significant difference between treatment and control group (p<0.05). Conclusion: CPP-ACPF pretreatment could increase GIC orthodontic bonding shear strength.Latar belakang: Lesi putih karies merupakan masalah utama selama perawatan dengan peranti cekat ortodonti. Hal ini dapat diatasi dengan cara mengurangi lesi putih sebelum perawatan dengan menggunakan bahan bonding yang mengandung fluorida. Aplikasi pasta casein phosphopeptides-amorphous calcium phospate fluoride (CPP-ACPF) sebagai bahan remineralisasi sebelum perawatan dan bahan bonding GIC diharapkan dapat mengatasi masalah ini sekaligus menambah kekuatan cekat bahan bonding GIC. Tujuan: Mengukur kekuatan geser piranti cekat ortodonti menggunakan bonding GIC dengan aplikasi pasta CPP-ACPF. Metode: 50 gigi premolar dibagi menjadi 2 kelompok, yaitu kelompok I sebagai kelompok perlakuan dan kelompok II sebagai kelompok kontrol. Setelah gigi dipotong dan ditanam dalam tabung akrilik, diaplikasikan pasta CPP-ACPF pada permukaan enamel sampel pada kelompok I selama 2 menit 2 kali sehari selama 14 hari. Aplikasi pasta CPP-ACPF tidak dilakukan pada kelompok kontrol. Kemudian breket ortodonti direkatkan dengan bahan bonding GIC pada semua sampel di kelompok I dan kelompok II. Kekuatan geser diukur dengan menggunakan alat Autograph Shimatzu dengan kecepatan cross head 0.5 mm/menit. Data dianalisis dengan statistik independent t-test. Hasil: Rerata kekuatan geser pada kelompok perlakuan 19,22 ± 4,04 MPa dan pada kelompok kontrol 12,97 ± 3,97 MPa. Analisis Independent t-test menunjukkan bahwa terdapat perbedaan signifikan antara kelompok perlakuan dan kontrol (p<0.05). Kesimpulan: Kekuatan geser antara piranti cekat ortodonti dengan bahan bonding GIC meningkat setelah aplikasi pasta CPP-ACPF.